(untitled) (Economic and Political Thought, 2019)
The article is a preliminary analysis of the economic conditions of health systems in Spain and Portugal. It describes their organisational structures and lists entities functioning in them. It presents changes that have taken place in the economic situation of both countries in recent years (including the impact of the global financial crisis that began in 2008) and the consequences that these changes have had for their health policy. The article lists the basic numbers referring to both systems and describes some organisational solutions improving their effectiveness. It also presents elements derived from before the democratic transformation, lowering this efficiency. Probably the most important of them are separate ‘subsystems’ of health care for some professional groups (including, for example, administration, the judiciary and army employees), which collaborate with common health care, but also hinder its uniform and clear operation. Probably to a large extent, as a result of leaving these elements in both systems and the related lack of sufficient optimisation of their operation, Portugal holds the 13th and Spain the 19th position in the European ranking of health systems – the Euro Health Consumer Index – examining these systems using fifty detailed criteria. A permanent prescription, used in Spain for many years, is worthy of more thorough research and transfer to the Polish healthcare system as it significantly reduces doctors’ workload not directly related to treatment, and consequently their shortage.